Applications of Surface-Surface Matching Algorithms for Determination of Orthodontic Tooth Movements - Keilig, L.; Piesche, K.; Jäger, A.; Bourauel, C. (Computer methods in biomechanics and biomedical engineering, 2003)
Orthodontic tooth movements are described as the differences between initial and final tooth positions. A computer based method for determination of tooth movements for different treatment methods was developed. A total of 20 casts of the upper jaw of patients treated with tooth positioners or fixed appliances were used as a basis for this study. Tooth movement was analysed on casts before (C i ) and after treatment (C f ). The casts were digitized either with a COMT or 3D laser scanning systems. After digitization, the models were superimposed in the palate by using a surface-surface matching algorithm. Tooth surfaces of the orthodontically moved teeth were segmented and determination of tooth movement was accomplished by matching the moved teeth from C i to C f . The resulting transformations delivered three dimensional information on translations and rotations. An accuracy of 0.2 mm in translations and 1 degree in rotations could be demonstrated, showing the different efficiency of treatment schemes.